Gastro-oesophageal reflux and idiopathic pulmonary fibrosis - Vancheri, C. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2013)
Idiopathic pulmonary fibrosis (IPF) is the most common of the idiopathic interstitial pneumonias. There is evidence of an increased prevalence of acid gastro-oesophageal reflux disease (GERD) in patients with IPF. Recent articles have focused on the potential role of chronic silent microaspiration in the pathogenesis of IPF. Aspiration in defined as the inhalation of gastric content into the larynx and lower respiratory tract. The reported use of GERD medications is an independent predictor of longer survival time in patients with IPF. These findings further support the hypothesis that GERD and chronic micro-aspiration may play important roles in the pathobiology of IPF.